Loading and Unloading Planning to Prevent Work Accidents on the AHTS Amber - Nurmala, Eka; Baihaqi, Baihaqi; Hartati, Diah Vitaloka; Darmayanti, Ni Luh; Saputra, Ilham (ALTAIR: Jurnal Transportasi dan Bahari, 2025)
The implementation of occupational safety and health principles is a very important element in a company's operations that cannot be ignored, because it is a key factor in supporting the efficiency of the production process and increasing productivity to strengthen the company's competitiveness. Work accidents during loading and unloading are accidents that occur when loading or unloading goods from vehicles or ships. The research here uses a qualitative descriptive approach, namely a research method that focuses on understanding the phenomenon in depth and through the process of collecting and analyzing non-numerical data, such as words, and narratives, and observations. The results of the study are: 1) Loading and unloading procedures at AHTS Amber include initial preparation, ship security, loading and unloading process, final inspection; 2) Obstacles in carrying out loading and unloading according to procedures at AHTS Amber include extreme weather conditions, ineffective coordination, technical conditions of equipment, safety factors, limited deck space, crew capacity, documentation and administrative procedures, cargo conditions; and 3) Management of loading and unloading planning at AHTS Amber in preventing work accidents including risk assessment and hazard identification, operational planning, training and simulation, equipment maintenance and inspection, effective communication, supervision and monitoring, implementation of safety management system (SMS).